A sensory evaluation of the preservation of chicken eggs using an herbal coating during cold storage - Saputri, Kade Wahyu; Nur'aini, Nur'aini; Hamka, Muhammad Subhan; Aziz, Arif Rahman (Politeknik Negeri Jember, 2025)
This study aimed to determine the sensory test of chicken eggs coated with herbal ingredients. This study used 240 0-day-old chicken eggs coated with herbal ingredients stored at cold temperatures of 4°C for 20 days. The treatment factors consisted of: T0: no coating (control), T1: coating eggshells with lemongrass solution, T2: coating eggshells with kaffir lime leaf solution, and T3: coating eggshells with pandan leaf solution. Sensory testing was carried out by boiling 20-day-old eggs for 8 minutes and the panelists assessed the color, aroma, taste, and texture. Data were analyzed using ANOVA with Duncan's multiple range test (DMRT) advanced test at a significance level of 0.05. Sensory testing showed that eggs without treatment (control) and egg coating using lemongrass solution, lime leaf solution, and pandan leaf solution did not significantly affect the egg yolk color, the egg white color, and the egg texture at the level of panelist preference. The egg taste and aroma coated with lime leaf solution had the lowest preference level. The conclusion of the sensory test of color, aroma, taste, and texture of eggs coated with lemongrass and pandan leaf solution was acceptable to the panelists.